'Quasi per speculum': vision, vigilance and the natural world in Dhuoda's Liber manualis. Issue 1 (1st January 2020) - Polanichka, Dana M.
ABSTRACT: From 841 to 843 CE, the Frankish noblewoman Dhuoda wrote a text for her son William that adopted two genres: the handbook and lay mirror. This article argues that vision and vigilance were central to the spiritual and political lessons that this mother taught her son. Dhuoda encouraged him to be watchful and observe the spiritual lessons offered by the natural world, especially plants and animals. Yet, she also insisted that William never mistake his earthly life (the quasi ) for his eternal existence in heaven. Dhuoda thus borrowed the trope of the vigilant king to urge her son to employ careful vision to avoid personal and political troubles, such as those engulfing his own family and the Frankish imperial family. By situating Dhuoda's use of quasi within her emphasis on vision and vigilance, this article offers deeper insight into this unique aristocratic woman and her troubling personal and political situations.